2015
DOI: 10.2147/ijn.s77118
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer paper-stacking nanofibrous membranes to deliver adipose-derived stem cells for bone regeneration

Abstract: Bone tissue engineering through seeding of stem cells in three-dimensional scaffolds has greatly improved bone regeneration technology, which historically has been a constant challenge. In this study, we researched the use of adipose-derived stem cell (ADSC)-laden layer-by-layer paper-stacking polycaprolactone/gelatin electrospinning nanofibrous membranes for bone regeneration. Using this novel paper-stacking method makes oxygen distribution, nutrition, and waste transportation work more efficiently. ADSCs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…As shown by FACS analysis, a homogenous adherent cell population was isolated by collagenase I digestion (Figure 1(c)); the isolated cells express mesenchymal antigens CD73, CD90, and CD105 and also were negative for HSC markers CD34, CD45, and CD14 (Figure 1(d)). Similar to previous studies, the expression profile of surface markers correlates with cell-based isolation with collagenase I digestion [27, 28]. Nevertheless, we found a discrepancy regarding CD90 expression, which according to Maddox et al, its expression in ADSCs is negative.…”
Section: Discussionsupporting
confidence: 88%
“…As shown by FACS analysis, a homogenous adherent cell population was isolated by collagenase I digestion (Figure 1(c)); the isolated cells express mesenchymal antigens CD73, CD90, and CD105 and also were negative for HSC markers CD34, CD45, and CD14 (Figure 1(d)). Similar to previous studies, the expression profile of surface markers correlates with cell-based isolation with collagenase I digestion [27, 28]. Nevertheless, we found a discrepancy regarding CD90 expression, which according to Maddox et al, its expression in ADSCs is negative.…”
Section: Discussionsupporting
confidence: 88%
“…The deposition of calcium phosphate in the 3D paper scaffolds described here are the first functional examples of template-guided mineralization by osteoblasts in a 3D system. Although in a previous report adipose-derived stem cells (ADSC) that were grown in polycaprolactone/gelatin electrospun nanofibrous membranes demonstrated regeneration of bone in a calvarial defect in a mouse model 42 , achieving mineralization by osteoblasts is a greater challenge due to their short life-span and possibility for de-differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The multilayer electrospinning technology adopted in our study was demonstrated to be capable of fabricating scaffolds meeting TE standards. The multilayer electrospinning method can further complement the advantages of the biomaterials with different functions, producing scaffolds with better flexibility, functionality, and plasticity 22,23 . In this study, we applied three materials, namely, PLGA, PVP, and PEO, and combined the benefits of the three to compensate for the limitations of each individual material, thus maximizing their respective advantages.…”
Section: Discussionmentioning
confidence: 99%